Islamic Education Philosophy: Epistemological, Anthological, Axiological Review, in the Quran, its benefits for humans in understanding themselves in carrying out life - Pramudya, Risqie Pramudya Endi (Jurnal Hadratul Madaniyah, 2025)
Islamic educational philosophy forms a conceptual foundation that integrates epistemology, ontology, and axiology into a holistic and transcendental education system. This study highlights that knowledge in Islam is not only derived from reason and experience but primarily from divine revelation as the highest and most authoritative source. Islamic educational ontology views humans as both spiritual and physical beings, tasked with worship and stewardship on earth. Axiologically, Islamic education upholds absolute, revelation-based values that serve as moral guidance in shaping students' character. The Islamic educational philosophy has proven to significantly contribute to character development, personal integrity, and cultural resilience amidst globalization. Empirical data indicate a marked increase in student discipline, social responsibility, and religiosity in institutions applying this philosophical approach. Thus, Islamic educational philosophy is not only normatively relevant but also practically effective in fostering a value-based civilization.